Role of Age, Sex, and Race on Cardiac and Total Mortality Associated With Super Bowl Wins and Losses - Kloner, Robert A. (Clin Cardiol, 2011)
BACKGROUND: Total and cardiac mortality rates in Los Angeles County, Califorina, increased after the 1980 Super Bowl loss (SBL), but there was an overall reduction in total mortality after the 1984 Super Bowl win (SBW). HYPOTHESIS: We hypothesized that age, sex, and race may have played a role in the Super Bowl related differences in death rates. METHODS: We compared mortality rates for SB‐related days with non‐SB control days assessing differences in demographics. We ran regression models predicting daily death rates per 100,000 including SB variable versus non‐SB control days for age, sex, race, and interactions for these covariates. RESULTS: After the SBL, daily death rates increased for both males and females. People aged ≥65 years had a larger absolute increase in all cause mortality during the SBL days compared with those aged <65 years, with significant interaction between age and SBL‐variable for all‐cause and cardiac‐related mortality. Whites and Hispanics had increased death rates on SBL days. There were trends suggesting less death in older patients and females associated with the SBW. CONCLUSION: A SBL triggered increased deaths in both men and women and especially in older patients, whereas a SBW reduced death more in those aged ≥65 years and in women. Copyright © 2011 Wiley Periodicals, Inc. The authors have no funding, financial relationships, or conflicts of interest to disclose.